Використання у закладах вищої освіти інноваційних технологій навчання - Орос Ільдіко; Orosz Ildikó; Oros Ildiko; Осередчук Ольга; Olga Oseredchuk; Біда Олена; Bida Olena (Видавництво «Код», 2025)
Резюме. Навчальний процес у закладах вищої освіти організовується з урахуванням науковопедагогічного потенціалу, матеріальної і навчально-методичної бази вищого закладу освіти, сучасних інноваційних технологій. Впровадження в закладах вищої освіти інноваційних технологій навчання співпало з глобальними процесами масштабної цифровізації та інформатизації суспільства. Зі збільшенням використання технологічних інновацій в повсякденному вжитку суттєво, підвищилася частка технологій в освітньому процесі вищої школи.

Abstract. The educational process in higher education institutions is organized taking into account the scientific and pedagogical potential, material and educational and methodological base of the higher education institution, and modern innovative technologies. The introduction of innovative learning technologies in higher education institutions coincided with the global processes of largescale digitalization and informatization of society. With the increasing use of technological innovations in everyday life, the share of technology in the educational process of higher education has increased significantly. Innovative learning technologies in higher education institutions are dictated by the popularization of informatization and digitalization of society. Having gone through the difficulties of the implementation stage, innovative learning technologies are under the close eye of scientific and pedagogical discourse in terms of their effectiveness. For a pragmatic analysis of the success of using innovative learning technologies, it is necessary to understand the human-dimensional and technologically oriented aspects of learning innovation. By studying the impact of all technological learning environments (distance, blended, mobile, virtual, gaming, etc.) on all participants in the higher education educational process (administration, faculty, higher education students), positive manifestations of innovative transformations were identified. The task of teachers of higher pedagogical educational institutions is to choose such forms and methods of teaching that would allow each student to show activity and creativity. That is, along with traditional forms and methods of learning, there are specific ones, which are disclosed in the article. The essence of innovative learning lies precisely in the fact that the educational process takes place under conditions of constant active interaction of all students.
Use of innovative learning technologies in higher education institutions
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-15
Keywords: інноваційне навчання; технології; інформатизація та цифровізація суспільства; вища школа; розвиток освіти